Demon of the air - Levack, Simon (London : Pocket, 2005)
Mexico-Tenochtitlan, in the year Twelve-House: the vast, teeming city of the Aztecs at the height of its glory. As the novel opens, the Chief Minister's trusted slave Yaotl is escorting a sacrificial victim up the steps of the Great Pyramid to celebrate the Festival of the Raising of Banners. Used to the bloodstained rites of the War-God's priests, Yaotl is unperturbed at the ritual slaughter of the so-called Flowery Death. When the victim runs amok and leaps to his death before he can be sacrificed, Yaotl's only worry is how to explain it to his master. But when more bodies start to appear and the Emperor Montezuma starts asking questions about the sorcerers who have vanished from his impregnable prison, Yaotl realises he needs answers soon. The secrets he uncovers will unlock nightmares from his own youth and threaten the future of everything he knows.
Originally published: London: Simon & Schuster, 2004.
Keywords: Aztecs -- Fiction; Mexico -- History -- Fiction. -- To 1519